Bstan bcos Zab mo naṅ don gyi gtoṅ thun rab gsal ñi maʼi sñiṅ po : a detailed study of Karma-pa Raṅ-byuṅ-rdo-rjeʼs famed treatise on the Anuttarayoga Tantra - Dkon-mchog-yan-lag, Źwa-dmar V, 1525-1583 (Delhi Karmapae Chodhey Gyalwae Sungrab Partun Khang, 1976)
General study of a treatise on the Buddhist tantric literature of the Anuttarayoga class.